Thermometric and Gravimetric Analyses of Aluminum Corrosion Control in a HCl Medium, Using Ricinus Communis Extract - Onukwuli,O.D. (2020)
This work presents the thermometric and gravimetric analyses of aluminum corrosion control in a HCl medium, using Ricinus communis (castor oil) extract. The obtained plant extract was subjected to phytochemical analyses for the identification of various sample constituents. Applying the thermometric technique, reaction values for the aluminum dissolution in free and inhibited HCl media were used to determine the extract inhibition efficiency. The gravimetric method was carried out using one factor at a time, and response surface methodology. Thermodynamic parameters of activation energy, heat of adsorption and free Gibbs energy of the corrosion inhibition process were determined. Central composite design of Design Expert Software was employed in the response surface methodology. The results analysis revealed that Ricinus communis extract contained phytochemicals of alkaloids, cardiac glycosides, flavonoids, phenolics, phytates, saponins and tanins. The extract adsorption onto the aluminum surface obeyed the physical adsorption mechanism; the activation energy was lower than the threshold value of 80 kJ/mol required for chemisorption. A quadratic model adequately described the relationship between the inhibition efficiency and the inhibitor concentration, temperature and time factors. The thermometric and gravimetric techniques recorded high inhibition efficiencies of 83.93% and 82.61%, respectively, showing that the Ricinus communis extract can be employed to control aluminum corrosion in an HCl medium.